Crack-up capitalism : market radicals and the dream of a world without democracy - Slobodian, Quinn, 1978- (2023)
"In a revelatory dispatch from the frontier of capitalist extremism, an acclaimed historian of ideas shows how free marketeers are realizing their ultimate goal: an end to nation-states and the constraints of democracy"--